Dinamika Sebaran Suhu Udara Menggunakan Citra Landsat 8 di Wilayah Denpasar Periode 2018-2021 - Pertiwi, Hanik Wahyu; Yuliara, I Made; Irmawan, Decky (Universitas Hamzanwadi, 2023)
Research has been conducted on the Dynamics of Air Temperature Distribution Using Landsat 8 Imagery for the 2018-2021 Period, in the Denpasar area study area with a location point at the Sanglah Geophysical Station. The methods used in this study were Normalized Difference Vegetation Index (NDVI) and Land Surface Temperature (LST), while the analysis used was correlation and validation. The results of the NDVI value study explained that from 2018 to 2021 the NDVI density value was getting higher so that the resulting temperature was low. Meanwhile, the determination of ESG on the dynamics of average air temperature explains that the average air temperature value in each year does not always rise linearly, in 2018 the highest average air temperature distribution was at 29.56 °C, in 2019 it was 35.56 °C, in 2020 it was 25.62 ° C and 2021 it was 30.72 ° C. In testing and analysis, a correlation relationship was obtained between Landsat 8 imagery (band 10 and band 11) and BMKG, which showed that the temperature between Landsat 8 imagery and BMKG was correlated in the same direction. The relationship between the distribution of average air temperatures with the implementation of PPKM in the Denpasar area has nothing to do with it as previously thought. Due to the increase in temperature, landsat 8 and BMKG images are only affected by the atmosphere